2018
DOI: 10.1038/s41598-018-24543-4
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous lancet-free monitoring of alcohol and glucose from low-volumes of perspired human sweat

Abstract: A lancet-free, label-free biosensor for simultaneous detection of sweat glucose and alcohol was demonstrated using zinc oxide thin films integrated into a nanoporous flexible electrode system. Sensing was achieved from perspired human sweat at low volumes (1–3 μL), comparable to ambient conditions without external stimulation. Zinc oxide thin film electrodes were surface functionalized with alcohol oxidase enzyme and with glucose oxidase enzyme towards developing an affinity biosensor specific to the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…4B ), with calibration curve inset, and shown to have an even wider range of sensitive detection in fig. S2 to accommodate expected sweat alcohol levels ( 36 , 37 ). The zinc sensor is tested in 0.001 M acetate buffer solutions of zinc (0, 400, 800, 1200, 1600, and 2000 μg/liter; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4B ), with calibration curve inset, and shown to have an even wider range of sensitive detection in fig. S2 to accommodate expected sweat alcohol levels ( 36 , 37 ). The zinc sensor is tested in 0.001 M acetate buffer solutions of zinc (0, 400, 800, 1200, 1600, and 2000 μg/liter; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[183][184][185] The research interest is mainly focused on the improvement of sensitivity, selectivity, adaptation to skin, and comfortability. [13,186] For example, Kim et al reported a stretchable diabetes monitoring patch consisting of an electrochemical glucose sensor and pH sensor (Figure 8a). [174] They innovated Ag doped graphene to improve the electrochemical sensitivity.…”
Section: Sweat Sensorsmentioning
confidence: 99%
“…Sensing was achieved from perspired human sweat at low volumes (1-3 μL), without external stimulation. Zinc oxide thin-film electrodes were surface functionalized with AOx, and alcohol monitoring was made by measuring impedance changes onto the sensor interface with a dynamic range between 0.01 and 200 mg dL −1 , with an LOD value of 0.01 mg dL −1 ethanol [39]. Electrochemical instruments for health monitoring using smartphones or similar devices have arisen in recent years.…”
Section: Organic Toxics: Alcoholmentioning
confidence: 99%